PENERAPAN SISTEM PAKAR UNTUK DIAGNOSA PENYAKIT PADA MANUSIA DISEBABKAN OLEH NYAMUK DENGAN METODE FORWARD CHAINING - Sapri, Sapri (Universitas Bina Darma, 2014)
The purpose of this study is make the application of expert systems in diagnosing diseases caused by mosquitoes. So the expert system can help physicians/nurses and lay people in making a conclusion on the symptoms of the disease suffered by the patient and can be developed further , and make it easy for users to find a solution. Stages of data collection are direct observation gets a medical at the General Hospital in the District Kepahiang Bengkulu province on diseases caused by mosquitoes . The workings of this system are user and login, main menu and the main menu is the content of the patient data , patient diagnosis, patient recap , recap patient diagnosis, and program information . Experts can make improvements in the form of knowledge the knowledge base and rule base, while the non- expert user can only use the facilities of the expert system.